Perancangan Sistem Informasi Pengarsipan Surat Perintah Pencairan Dana pada Kas Daerah Berbasis Web (Studi Kasus Badan Keuangan Aset Daerah Kabupaten Bandung Barat) - Delisa Aprilia; Nurul Anisa; Karyadi .; Johni S Pasaribu (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Information systems at this time will continue to grow from various aspects, to take advantage of the progress in this era of information systems into a need that must be owned by every agency.One of them is the filing information system, each agency needs to keep documents as important records of various activities.Therefore, the archive must be managed properly so that it is not difficult when searching for the required information.In addition, the archive system can be used in the long term so as to avoid some obstacles that often occur in the management of archives such as damaged, scattered or lost.This archive system was created to facilitate the filing process, because Kasda BKAD archiving is still manually.Therefore, in this study was carried out the design of a filing information system for Disbursement Warrants (SP2D) in Regional Cash (Kasda) in BKAD West Bandung Regency. The development of this system uses waterfall methods and functional design using UML (Unified Modelling Language), the results of black box system testing are obtained valid results..This research produces a web-based information system that is expected to make it easier to manage archives.